Measurement of Vapor Liquid Equilibrium for Difluoromethane (R32) +Fluoroethane (R161) + 2,3,3,3-Tetrafluoroprop-1-ene (R1234yf) - Yang Tao; Hu Xiaozhen; Meng Xianyang; Wu Jiangtao (Zhileng xuebao, 2018)
In the study, we focused on the vapor-liquid equilibrium property of the ternary system of R32+R161+R1234yf. The vapor–liquid equilibrium data was measured via a liquid-circulation apparatus at temperatures from 283.15 K to 323.15 K. The standard uncertainties of temperature, pressure, and mole fractions were 10 mK, 0.5 kPa, and 0.005, respectively. The Peng–Robinson–Stryjek–Vera (PRSV) equation of state (EOS) combined with the Wong–Sandler (WS) mixing rule and non-random two-liquid (NRTL) activity coefficient model were employed to predict the ternary vapor–liquid equilibrium properties by using the parameters of the binary mixture (i.e., R32+R161, R32+R1234yf, and R161+R1234yf). The average absolute deviation of pressure AADp (average absolute deviation) is 0.34%. Additionally, the average absolute deviation of vapor phase mole fractions for R32 (AADy1) and R161 (AADy2) are 0.002 and 0.001, respectively, and thus the predicted values for the ternary system exhibit good agreement with the experimental results.